2013
DOI: 10.1007/s00394-013-0519-5
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus casei Zhang ameliorates high-fructose-induced impaired glucose tolerance in hyperinsulinemia rats

Abstract: Lactobacilluscasei Zhang administration exert both preventive and ameliorative effect on oral glucose tolerance AUC in IGT rats but may be via different mechanisms. L.casei Zhang could prevent rats from increased AUC through GLP-2 lowering, while the ameliorative effect in high-fructose-fed post-adolescent rats may be via B. fragilis enriched vitamin K2-dependent osteocalcin mechanism in which AdipoR2, LXR-α and PPAR-γ signaling were involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 41 publications
1
51
0
Order By: Relevance
“…Interestingly, in our model the administration of L. kefiri completely prevented the alterations caused by FRD intake, which strongly support the beneficial effect of this probiotic. In concordance with our results, other studies have shown that the use of Lactobacillus species as probiotics improves the metabolic disorders induced by the FRD [49,50]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in our model the administration of L. kefiri completely prevented the alterations caused by FRD intake, which strongly support the beneficial effect of this probiotic. In concordance with our results, other studies have shown that the use of Lactobacillus species as probiotics improves the metabolic disorders induced by the FRD [49,50]. …”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, Zhang et al reported that FRD supplemented with L. casei , increased intestinal Bacteroides fragilis ( Bacteroidetes phylum) and decreased Clostridium spp. ( Firmicutes phylum) quantities, at the same time that it improved the oral glucose tolerance test in FRD-fed rats [50]. In line with these results, FRD-fed mice supplemented with L. kefiri showed an increase in B. fragilis , but no changes in Clostridium coccoides group, accompanied by an improvement of several metabolic alterations caused by FRD intake.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Liver glycogen contents were significantly decreased ( p  < 0.05). In therapeutic group, L. casei Zhang administration possessed improved glucose tolerance ( p  < 0.05), which were associated with increased osteocalcin level ( p  < 0.01), improved intestinal bile acids secretion ( p  = 0.060), decreased serum MDA levels ( p  < 0.05) and upregulation of LXR-α, PPAR-γ and AdipoR2 gene expression.[64] Lactobacillus reuteri GMNL-263High levels of serum glucose, insulin, leptin, C-peptide, glycated hemoglobin, GLP-1, liver injury markers, lipid profile in serum and liver in high-fructose-fed rats were significantly suppressed after Lr263 administration. Feeding of Lr263 reversed the decreased number of bifidobacterium species and lactobacillus species and increased number of clostridium species induced by high fructose treatment.…”
Section: Probiotic Lab and Type-2 Diabetes Treatmentmentioning
confidence: 99%
“…In our previous work, we demonstrated that Lactobacillus casei Zhang could enrich Bacteroides fragilis and stimulate adiponectin receptor 2 signaling [17]. It has reported that vitamin K2 also enrich Bacteroides and vitamin K2-dependent osteocalcin can increase adiponectin expression[1819].…”
Section: Introductionmentioning
confidence: 99%